Dual-Mechanism Study of Metal-Free g-C3N4 Catalysts for Advanced Oxidation Under Non-Photocatalytic Conditions - Zixu Yang; Yang Sun; Weizhi Wang; Xiaohan Yuan; Pengfei Tian; Jing Xu (Molecules)
Metal-free materials have been proved to be promising replacements of traditional metal-based catalysts for advanced oxidation reactions. Carbon nitride was found to be able to activate H2O2 and generate hydroxyl radicals (•OH). Nevertheless, the performance of carbon nitride is highly dependent on an external light source. In this work, we report a light-independent, metal-free catalyst based on g-C3N4 prepared using a facile calcination method. It is revealed that two reaction pathways, a radical (•OH) one and a nonradical (H2O2) one, coexist in organics oxidation on g-C3N4. The dominant reaction pathway is dependent on the condensation temperature of UCN. In addition, this g-C3N4 exhibited excellent stability after being recycled and reused for five cycles. The findings in this work can be used for the design of efficient and robust metal-free catalysts with both superior catalytic performance and high stability for various heterogeneous catalytic processes.